Difficult discussions : issues and ideas for engaging college students in peace and justice topics - Finley, Laura L. (Peace education., 2020)
"Drawing from many disciplinary areas, this edited volume shares tools, techniques and ideas for engaging college students in difficult discussions. From sexual violence to race to poverty and more, chapters in the book present useful strategies as well as limitations in creating safe classroom spaces. Ideal for peace and justice educators, this volume also includes the voices of students in every chapter"--